Strategi Masyarakat untuk Mengatasi Kerawanan Pangan di Desa Pitay Kecamatan Sulamu Kabupaten Kupang - Cristianus Irvan A. Dhoy; Utma Aspatria; Rut Rosina Riwu (Media Kesehatan Masyarakat, 2021)
Household food security is related to the ability of the household to fulfill the needs of all its members. This implies physical and economic access to food that is sufficient, safe, and culturally acceptable in terms of the quantity and quality of nutrition to meet the needs of each family member. Pitay Village is one of the villages that is at risk of food vulnerability because it does not meet the three indicators namely availability, access and utilization. This study aims to determine the community's strategy to overcome food insecurity in Pitay Village, Sulamu District, Kupang Regency. This type of research was descriptive quantitative. The population in this study were 250 household heads. The sample consisted of 72 families determined using the Slovin formula. The results showed that 56.9% of respondents experienced food insecurity and 55.6% of respondents ate food from the forest as a strategy to deal with food insecurity. Local governments need to provide social assistance as well as increase entrepreneurial interest by providing working capital funds. Socialization and empowerment for productive age groups related to the use of homeyard (green house program) are recommended to meet household food needs.